Education transformation in era 4.0: The effect of learning facilities on student learning outcomes - Desi Handrayani; Kurniati Rahmadani; Fuad Abdul Baqi; Gulzhaina Kuralbayevna Kassymova (Journal of Computer-based Instructional Media, 2023)
This study aims to determine the effect of learning facilities on the learning outcomes of SMK Pasundan 1 Serang City class XI students. The sample of this research is class XI students of SMK Pasundan 1 Serang City, with as many as 61 people who act as respondents. To answer questions from the formulation of the problem above, the type of research used is quantitative. In contrast, the data collection technique uses questionnaires, observation, and documentation, and the data analysis technique uses SPSS IBM 26. The results of hypothesis testing research using validity test, reliability test, normality test, linearity test, T-test, and F test show that learning facilities obtained the results of tcount 8.257> ttable 2.002 (sig 0.000 <0.05), meaning that H0 is rejected and Ha is accepted. Thus, it can be concluded that there is an influence between learning facilities on the learning outcomes of class XI students of SMK Pasundan 1 Serang City.